Color-tunable phosphor of Sr3YNa(PO4)3F:Tb3+via interionic cross-relaxation energy transfer. Issue 45 (16th July 2018) - Zhang, Bingye; Ying, Shitian; Han, Lu; Zhang, Jinsu; Chen, Baojiu
Abstract : Color-tunable Sr3 YNa(PO4 )3 F:Tb 3+ phosphors were obtained via cross-relaxation energy transfer, and exhibit superior thermal stability. Abstract : A series of color-tunable Sr3 YNa(PO4 )3 F:Tb 3+ phosphors with a fluorapatite structure were synthesized by a traditional high-temperature solid state reaction. The emitting color tuning from blue to green can be observed by gradually increasing Tb 3+ concentrations, which is attributed to the enhanced cross-relaxation (CR) between Tb 3+ ions, as described by ( 5 D3, 7 F6 )–( 5 D4, 7 F0 ). The CR process is analyzed based on the Dexter and Inokuti–Hirayama model, which is assigned to the electric dipole–dipole interaction. The energy transfer critical distance between Tb 3+ ions is evaluated to be 18.1 Å. In addition, the thermal quenching mechanism of Sr3 YNa(PO4 )3 F:Tb 3+ is also investigated. At the general working temperature of an LED (423 K), the luminescence intensity still maintains 81% and 92% with the Tb 3+ concentration of 10 and 30 mol%, respectively, indicating an excellent thermal quenching performance of Tb 3+ . Due to the good optical and thermal properties, the Sr3 YNa(PO4 )3 F:Tb 3+ phosphor can be used as a promising green emitting phosphor candidate in the field of white light applications.